2010
DOI: 10.1111/j.1476-5381.2009.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin in sepsis and systemic inflammation: a harmful biomarker and a therapeutic target

Abstract: The worldwide yearly mortality from sepsis is substantial, greater than that of cancer of the lung and breast combined. Moreover, its incidence is increasing, and its response to therapy has not appreciably improved. In this condition, the secretion of procalcitonin (ProCT), the prohormone of calcitonin, is augmented greatly, attaining levels up to thousands of fold of normal. This hypersecretion emanates from multiple tissues throughout the body that are not traditionally viewed as being endocrine. The serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
221
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(243 citation statements)
references
References 126 publications
3
221
0
9
Order By: Relevance
“…According to studies, procalcitonin in bacterial diseases is reported to increase rapidly in a short time after TNF-α, IL-6 and IL-8. It is known by various researchers that in septicemias, procalcitonin could increase as one hundred times more than normal serum levels [2,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies, procalcitonin in bacterial diseases is reported to increase rapidly in a short time after TNF-α, IL-6 and IL-8. It is known by various researchers that in septicemias, procalcitonin could increase as one hundred times more than normal serum levels [2,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated with various studies that the determination of serum procalcitonin amount caused by bacterial inflammations compared to other cytokines is more specific and sensitive [2,[15][16][17][18][25][26][27] .…”
Section: Measurementsmentioning
confidence: 99%
“…4 Previous studies found that there were increasing level of procalcitonin in trauma patients. 4,8,9,10 It had peak concentration after trauma on the first and third day. 4 It is thought that procalcitonin can be used to observe inflammatory status on trauma patients.…”
Section: Increasing Procalcitonin Level Of Blunt Thoracoabdominal Tramentioning
confidence: 99%
“…Systemic inflammatory syndrome of non-infectious etiologies also leads to increases in serum PCT levels though increased serum PCT levels may be present without any evidence of severe infection in patients subsequent to major trauma or surgery as well as postcardiopulmonary bypass. However, the median values under these conditions are usually lower than those found during severe sepsis and septic shock [68][69][70][71][72][73][74].…”
Section: Procalcitoninmentioning
confidence: 99%